The Effects of Imposed Business Relocation on Service Delivery at Uganda Christian University, Mukono - Babra Aleto (Uganda Christian University, 2026)
The research design of this study was based on the convergent parallel mixed design. The quantitative data were collected from the respondents through the use of structured questionnaires, whereas the qualitative data were collected from the targeted business owners through the interview method. The quantitative data were analyzed using the descriptive statistical method, including frequencies, percentages, means, and standard deviations, from the total sample of the study, which comprised respondents. The research study was prompted by the concern that the physical expansion of the university and the relocation of the vendors from the campus could influence the provision of services at the university, especially to the students and the staff at the Uganda Christian University located in Mukono. The findings indicated that imposed relocation had a moderate negative influence on the accessibility of the services, mainly in terms of increased levels of inconvenience and time spent traveling. Businesses experienced temporary operational disruptions during the period of transition, including the reduction of customer flow and workflow adaptation. Customer satisfaction was also negatively impacted moderately following the imposed relocation, mainly due to the reduction in levels of convenience and communication rather than the quality of the services provided. Although adaptation strategies were put in place, the services were still not at the levels of convenience before the relocation at the time of the study. The study concludes that imposed business relocation has a moderate influence on the delivery of services at Uganda Christian University. The study also recommends that planning for relocation, communication systems, strategic positioning of vendors, and support mechanisms should be put in place to ensure the smooth delivery of services during the time of expansion.
Undergraduate research